Ammonia Toxicity to Rinuak (Gobiopterus brachypterus) of Lake Maninjau - Gunawan Pratama Yoga; Octavianto Samir (Indonesian Journal of Limnology, 2020)
Rinuak (Gobiopterus brachypterus) has an important economic value for local communities in Lake Maninjau - West Sumatra. The catch of G. brachypterus is decreasing along with the decline of the water quality.  Ammonia is considered one of the most toxic pollutants in the aquatic ecosystem. It can be produced from the natural decomposition of organic matter or excreted by aquatic organisms as a nitrogenous waste product. Therefore, the information about toxicity ammonia in G. brachypterus is important as a management tool for fish conservation in Lake Maninjau. This research was aimed to find the LC50 value of ammonia in G. brachypterus. A static acute toxicity test was conducted for 96 hours. The fish were exposed to different test chemical concentration level for 96 hours, under static conditions. Mortality was recorded and concentration killed 50% of the fish was determined as LC50-96h, No Observed Effect Concentration (NOEC), and Lowest Observed Effect Concentration (LOEC). Values of LC50-96h, No Observed Effect Concentration (NOEC) and Lowest Observed Effect Concentration (LOEC) were 11.62 mg/L TAN or 0.27 mg/L NH3, 5 mg/L TAN or 0.12 mg/L NH3 and 16 mg/L TAN or 0,37 mg/L NH3, respectively. Ammonia’s Maximum Acceptable Tolerant Concentration (MATC) for G. brachypterus was 8.9 mg/L TAN or 0.21 mg/L NH3. The acute toxicity result showed that Rinuak (G. brachypterus) was sensitive to ammonia. The information about ammonia toxicity data is important for the determination of water quality guidelines in Lake Maninjau.